On the pressure approximation in nonstationary incompressible flow simulations on dynamically varying spatial meshes - Besier, Michael; Wollner, Winnifried (International journal for numerical methods in fluids, 2012)
The subject of this paper is a defect in the approximation of the pressure on dynamically changing spatial meshes in the computation of nonstationary incompressible flows. The observed behavior is due to the fact that discrete solenoidal fields lose this property under changes of the spatial discretization. This phenomenon is analyzed for DG finite element discretizations in time, and possible ways are considered to circumvent this problem. Copyright © 2011 John Wiley & Sons, Ltd.